THE CRITICS OF THOMAS LICKONA’S CHARACTER EDUCATION: ISLAMIC PSYCHOLOGY PERSPECTIVE - Yandi Hafizallah (Department of Islamic Psychology, The State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, Indonesia, 2020)
This paper aims to explain the concept of Thomas Lickona's character education based on the study of Islamic psychology. Thomas character education is an educational design oriented to moral knowledge, moral feelings, and moral action. Overall character education can be defined as a way of thinking and behaving based on aspects of knowledge (cognitive), feelings (feeling), and action (action). Islamic psychology is considered relevant in examining aspects of psychology contained in Thomas Lickona's character education. Islamic psychology is literally a science that discusses human behavior and soul based on an Islamic perspective. The existence of a paradigm similarity in the character education of Thomas Lickona and Islamic Psychology is in terms of moral values ​​in Islam called morality. Islamic psychology has three concepts on how to implement a value, namely, aspects of Jismiah, Nafsiyah, and Ruhaniah are concepts in character building, which means there will be integrated structures in realizing the ideal character shape in the scientific frame of Islamic psychology